Photochemical Vapor Generation Based Accurate Determination of Cadmium in Wastewater Using Novel Photoreactor and Gas-Liquid Separators Using Flame Atomic Absorption Spectrometry with Matrix Matching Calibration - Buyukpinar, Cagdas; Bodur, Suleyman; San, Nevim; Komesli, Okan Tarik; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2021)
Cadmium is widely applied in various industrial areas and poses serious problems to human health such as cancer. Many analytical methods are used to determine this toxic element at trace levels, and new methods such as photochemical vapor generation (PVG) offer a different perspective. In this study, a photochemical vapor generation-based method was developed and combined with flame atomic absorption spectrometry (FAAS) for the determination of cadmium in wastewater. To achieve this goal, low molecular weight organic acid type and concentration, ultraviolet (UV) irradiation period and gas-liquid separator design parameters that directly affect the analytical performance of the method were optimized. Under the optimum conditions, the limits of detection and quantification were 0.19 and 0.65 mg/L, respectively. In spike experiments carried out with wastewater samples, the recovery values were between 96 and 110%, showing high accuracy. Low values for the relative standard deviation also indicated good precision for replicate measurements.
Keywords: Cadmium; flame atomic absorption spectrometry (FAAS); photochemical vapor generation; wastewater; Chemistry